Land use planning in provision of affordable housing for middle income households in Kuala Lumpur, Malaysia - Che Hassan, Intan Melati (2019)
The literature review identifies a particular problem concerning housing affordability among middle-income earners in Kuala Lumpur, Malaysia. Realising that affordable housing accessibility is an acute problem among the middle-income group; the government has initiated several policies and housing programs. Advocates believe that successful growth management can provide housing for the middle-income households via effective and comprehensive planning through the adoption of appropriate land use planning and housing policies.